Standardisation of neonatal prescribing in the east of england. (7th June 2011) - Stone, S; Muthukumar, P; Gooding, N; Farrer, K
Abstract : Background: The East of England (EoE) perinatal networks have 18 neonatal units including three network neonatal intensive care units. Different units historically have used different drug infusion policies. For transferred babies this increases stabilisation time, costs and risks from infection and medication error. Aims: (1) Survey the infusion concentrations used across the region. (2) Agree and implement regional unified drug prescribing. Method: Between June and October 2009 an email questionnaire was sent to pharmacists and lead nurses in all regional neonatal units requesting prescribing information for their top 10 drug infusions and the types of pumps and syringes used. Survey results: Data indicated a wide range in prescribing protocols for the top 10 drug infusions. Practice change: The results were discussed at network board meetings, clinicians development groups and the neonatal transfer user group. Proposals for unified drug infusion concentrations, with introduction of standard syringe labels were reviewed and accepted for implementation across the region from April 2010. Prospective monitoring and audit is on-going to ascertain the extent of consequential quality improvements. Conclusion: Widespread variation in prescribing practice poses increased risk and costs. Collaborative agreement across the region has enabled introduction of a unified prescribing policy for the common drug infusions, prescription practice and necessary equipment. We believe this will improve the quality of care by reducing costs, the transfer stabilisation time and risks of medication error while actively supporting the national QIPP agenda.